Buschke scleredema: A case report - Ahmed, Shahid; Mushtaq, Kanwal; Sulehri, Zareen Saqib; Chaudry, Arslan (Journal of Pakistan Association of Dermatologists, 2020)
Scleredema is a rare skin disease â€œprogressive hardening of the skinâ€ as the cardinal feature. Here we report a case in a four year old girl with this rare condition